1993
DOI: 10.1007/bf01974343
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the effects of various hepatotoxic compounds on urinary and liver taurine levels in rats

Abstract: The effect of various hepatotoxicants on urinary taurine and urinary creatine has been studied in the rat. Several hepatotoxic agents, carbon tetrachloride, thioacetamide, galactosamine and allyl alcohol which all caused hepatic necrosis (sometimes accompanied by steatosis), resulted in a rise in urinary taurine and in some cases creatine, when administered to rats. Ethionine and hydrazine also raised urinary taurine but caused only steatosis and did not raise urinary creatine. Therefore urinary taurine and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
87
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 21 publications
6
87
2
Order By: Relevance
“…Therefore, the reduced production of ATP may lead to a reduced formation of hippurate in the combined group as observed in the present study. In addition, the levels of taurine and creatine in the urine were increased significantly in the combined group, and the combined elevations in the levels of taurine and creatine had been found previously as a biomarker for liver damage (Waterfield et al, 1993;Beckwith-Hall et al, 1998). In summary, the present investigation has demonstrated that combined exposure to PCBs and TCDD induced significant hepatotoxicity in rats, and mitochondrial dysfunction and fatty acid metabolism perturbation might contribute to the hepatotoxicity.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, the reduced production of ATP may lead to a reduced formation of hippurate in the combined group as observed in the present study. In addition, the levels of taurine and creatine in the urine were increased significantly in the combined group, and the combined elevations in the levels of taurine and creatine had been found previously as a biomarker for liver damage (Waterfield et al, 1993;Beckwith-Hall et al, 1998). In summary, the present investigation has demonstrated that combined exposure to PCBs and TCDD induced significant hepatotoxicity in rats, and mitochondrial dysfunction and fatty acid metabolism perturbation might contribute to the hepatotoxicity.…”
Section: Discussionsupporting
confidence: 84%
“…Individual modulations in the levels of urinary taurine and -alanine have been previously reported as biomarkers of general hepatotoxicity, although the excretion of the latter has been attributed to concomitant renal failure. 37 The dependencies linking hippurate with citrate and with 2-OG ( Figure 2C) also identify a shared cellular compartment (mitochondria); here, benzoic acid of gut microbiotal origin 17 is conjugated with glycine via a mitochondrial acetyl-Coenzyme A activation step to form hippuric acid, 38 in colocation with the topographical center for TCA cycle activity. This illustrates the ability of in vivo interactome maps to transcend species boundaries and allow virtual linkage of the mammalian primary metabolome (under host genomic control) with the cometabolome, which is partly under symbiotic gut microbial control.…”
Section: Resultsmentioning
confidence: 95%
“…36 • Taurine is a primary biomarker of liver dysfunction, and -alanine is a surrogate biomarker for liver damage; therefore, they should vary in concert in response to liver injury. 37 methylamine to acetate These both relate to the gut microbiotal effect on metabolism. 42 Methylamines derive from microbiotal conversion of choline and are associated with liver toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of oxidative stress in natural cases of hepatic glycogen degeneration [3] indicated that the effect on hepatic antioxidant parameters in the current study may be attributed to ethionine. Ethionine was reported to affect the glutathione metabolism in rat liver a short period after injection, which varied from 4 hr [25] to 24 hr [10] followed by significant increase in 2 days [19] or 3 days [24]. Furthermore, the administration of ethionine induced an increase in the synthesis of the H 2 O 2 -generating peroxisomal beta-oxidation enzyme system in the rat liver.…”
mentioning
confidence: 98%
“…In addition, underfeeding in cattle was reported to induce changes in the antioxidant systems in the liver [16]. The liver glutathione level in hepatic dysfunction induced by ethionine was extensively studied in rats [10,19,24,25]. It was reported that erythrocytic oxidative stress increased in human patients with severe hepatic disease [17,26].…”
mentioning
confidence: 99%